(untitled) (Journal of Economic Research & Business Administration, 2015)
Accounting standards – this is the second level of regulation of the accounting system, they are legal documents, mandatory for all organizations representing the financial statements. Based on the standards set bazvye accounting rules on certain sections of the account, as well as industry and other organizations in the part Highlights The main purposes of this research is the justification of necessity for transition of the accountancy system to international standards of financial reporting, and scientific problem solving and working out the way of improvement of enterprises’ accounting system of RK, tailored to modern conditions. The origi The originality of research is in obtained scientific results showing the role and meaning of financial reporting formed as per IFRS as the base for managerial decision making. The problems of transition of accountancy system and financial reporting of RK onto international standards and the ways of how to solve them are examined.